2016
DOI: 10.18632/oncotarget.12329
|View full text |Cite
|
Sign up to set email alerts
|

RAB22A overexpression promotes the tumor growth of melanoma

Abstract: Malignant melanoma is the most aggressive type of skin cancer. RAB22A, a member of RAS oncogene family, has been found to be significantly upregulated in multiple human cancers. In the present study, we found that RAB22A mRNA expression was significantly upregulated in melanoma tissues (including 60 primary melanomas and 84 metastatic melanomas) compared to benign nevi (n = 20), which were significantly higher in metastatic melanoma tissues than primary tissues. Immunohistochemistry data further showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…It was also observed that transfection with the miR-203 specific inhibitor or culture of cells under an extrinsic hypoxia condition (1% O 2 ) significantly increased the RAB22A transcription. The results were consistent with previous reports 4,26. However, the promoting effects by an extrinsic hypoxic condition (1% O 2 ) on the levels of RAB22A transcription were mitigated by treatment with 3f (Fig.…”
Section: Resultssupporting
confidence: 93%
“…It was also observed that transfection with the miR-203 specific inhibitor or culture of cells under an extrinsic hypoxia condition (1% O 2 ) significantly increased the RAB22A transcription. The results were consistent with previous reports 4,26. However, the promoting effects by an extrinsic hypoxic condition (1% O 2 ) on the levels of RAB22A transcription were mitigated by treatment with 3f (Fig.…”
Section: Resultssupporting
confidence: 93%
“…With increasing malignancy and a poor prognosis, RAB22A is highly expressed in various types of cancer. For instance, Su et al demonstrated that the upregulation of RAB22A promoted melanoma cell growth (29). Proliferative effects can be observed from gastric and colorectal cancer cells via the silencing miR-204-5p expression which also targets RAB22A (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…A further study performed by Qi et al (33) identified that the transmembrane protein, YIPY2, promotes cd147-medated malignant phenotypes by recruiting and activating Rab5 and Rab22a in hepatocellular carcinoma. Su et al (17) found that the increased expression of Rab22a is related to an advanced clinical stage in melanoma and shorter OS. The present study suggests that Rab22a may act as a novel oncogene in Bc and may be a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…The staining intensity as well as positive staining percentage of tumor cells were used for evaluation. The intensity of staining was categorized as previously described (17): 0 (stainless), 1 (light yellow), 2 (yellow brown) and 3 (brown). The proportion of positive staining tumor cells were 0 (0%), 1 (1-10%), 2 (11-25%), 3 (25-50%) and 4 (>50%).…”
Section: Patients and Samples A Total Of 258 Samples From Female Patmentioning
confidence: 99%